2018
DOI: 10.1016/j.ridd.2018.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory study on cognitive abilities and social responsiveness in children with 22q11.2 deletion syndrome (22q11DS) and children with idiopathic intellectual disability (IID)

Abstract: Results reflect similar cognitive and social responsiveness profiles and trajectories across groups with children with 22q11DS being more at risk for growing into a social deficit. We recommend repeated monitoring of social skills development to adapt the environmental demands to the child's individual social capacities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 49 publications
(86 reference statements)
1
20
0
Order By: Relevance
“…Growing into deficit or developmental lag refers to patients who are making insufficient progress with increasing age, resulting in a growing discrepancy in relation to their typically developing peers. They develop at a slower pace compared to the general population causing decreased scaled and standard scores on certain subtests (Swillen & McDonald‐Mcginn, 2015; Van Den Heuvel et al, 2018). As shown in Figure 2, PIQ and VIQ trajectories are comparable to those of FSIQ, although patient 11 obtains remarkable higher PIQ than FSIQ scores at the second time point, which can be regarded as a catch up on the performance domain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing into deficit or developmental lag refers to patients who are making insufficient progress with increasing age, resulting in a growing discrepancy in relation to their typically developing peers. They develop at a slower pace compared to the general population causing decreased scaled and standard scores on certain subtests (Swillen & McDonald‐Mcginn, 2015; Van Den Heuvel et al, 2018). As shown in Figure 2, PIQ and VIQ trajectories are comparable to those of FSIQ, although patient 11 obtains remarkable higher PIQ than FSIQ scores at the second time point, which can be regarded as a catch up on the performance domain.…”
Section: Resultsmentioning
confidence: 99%
“…This increasing cognitive deficit with age needs to be interpreted with caution, since it might be partially caused by measurement confound or age range differences. However, growing into deficit is often observed in children with CNVs (Swillen & McDonald‐Mcginn, 2015; Van Den Heuvel et al, 2018) and may be partially explained by the increasing proportion of abstract reasoning skills in IQ tests when children grow older. This finding is in line with the observation that an increasing number of 22q11.2 dup patients need additional educational support or even change from regular to special education with increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the underlying polygenic haploinsufficiency, 22qDS is a multisystem disorder with highly variable and complex phenotypic expression that can vary over the course of development (7,41). Most 22qDS patients (60-80%) cope with at least one lifelong psychiatric disorder, and many patients display comorbid psychopathologies (41).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to intellectual disability and several anatomic phenotypes, psychiatric diagnoses include depression (2), obsessive-compulsive disorder (3), schizophrenia (4), attentional deficit hyperactivity disorder, and autism spectrum disorder (5). Among their constellation of symptoms, 22qDS patients often display pronounced social cognition impairments (6,7), and performance in the social cognitive domain is one of the best measures of the patients' overall quality of life (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…However, differences in non-social neurocognitive abilities, such as executive functioning, could in part account for differences in social cognitive performance (5,15). Prior studies have also found that impairments in both social cognition and social skills are more pronounced in children and adolescents with 22q11DS than in children with general developmental delays or idiopathic intellectual disability, as well as compared to other genetic conditions such as Williams Syndrome (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%